Dehydration of fructose to 5-hydroxymethyl furfural over ordered AlSBA-15 catalysts - Lucas, Nishita; Kokate, Ganesh; Nagpure, Atul; Chilukuri, Satyanarayana V. (Microporous and Mesoporous Materials, 2013)
5-Hydroxymethyl furfural is an important platform chemical. It is successfully synthesized from renewable carbohydrates using mesoporous AlSBA-15 catalysts under biphasic conditions. Fine tuning of the catalyst acidity is important to drive the reaction to give good yields of furan compound. Al-SBA-15 catalysts with different Si/Al ratios were prepared and characterized by XRD, Al-27 MASNMR, SEM, TEM, N-2 sorption, ICP-OES and TPD of ammonia. Results show that part of aluminium is substituted into tetrahedral positions. The catalyst with lower acid site density but medium to strong acid strength favours selective formation of HMF. Under the optimized conditions, HMF selectivity was as high as 88% at 59 mol% conversion of fructose. Leaching of part of aluminium occurs under hydrothermal conditions, if solvent mixtures containing water are used, while activity can be retained if DMSO is used as solvent. (c) 2013 Elsevier Inc. All rights reserved.
Keywords: Acidity; AlSBA-15; dehydration; fructose; Hydroxymethyl furfural